CHARACTER EDUCATION MANAGEMENT FOR CHILDREN WITH SPECIAL NEEDS AT MULTI TALENTA ELEMENTARY SCHOOL - ummi kultsum (BAIK Publishers, 2025)
The opportunity given to children with special needs to learn together with other children in a school is given in inclusive education services. Inclusive education is expected as an effort to absorb the various abilities of students who have various differences and potentials and to provide support to enable them to participate in regular education activities as much as possible. Inclusive education can be an appropriate means of instilling students' character values to appreciate differences, foster an attitude of caring, increase a sense of mutual cooperation and tolerance among others. The method used in this research is descriptive qualitative. This research aims to describe the management of character education for children with special needs at Multi Talenta Elementary School. The things studied include the process of planning, organising, implementing and assessing character education. The subjects in this study included the principal, homeroom teacher, accompanying teacher, children with special needs coordinator, students and guardians of Multi Talenta Elementary School. The results of this study show that the process of managing character education starting from the planning, organising, implementing and assessing process has gone well, this is in line with the support of all the resources involved, namely from the school, parents, family and community environment. Multi Talenta Elementary School has 13 character values that have been applied to activities in the form of learning, habituation, example and reinforcement. The teachers have provided good service and assistance according to the needs of students.